After the Tempest: The Post-Holocaust years in the Netherlands and in Greece - Benveniste, Henriette-Rika; Hantzaroula, Pothiti (Historein, 2019)
This special issue of Historein offers new documentation and insights in a new area of historical research by contextualising different aspects of Jewish history in the Netherlands and in Greece: efforts to come to terms with sadness and loneliness due to the loss of the family, restitution struggles, disillusionment and hopes, persisting antisemitism, and political constraints. Any effort to better understand those years has to overcome traditional constraints and divisions between “internal” and “external” histories of the Jewish communities. Our issue points in the direction of the transnational approach. The dismantling of narratives that subsumed Jewish victims and their experiences under the general battle against fascism formed the basis for comparative studies that use various axes around which research questions revolve: time as a parameter for understanding the shifts in identities in relation to political and social contexts, the development of welfare politics that emerged as an antidote to the catastrophe, the generational experiences that established new memory frames, and the responses to conflicting memories. We need, at the same time, to remind ourselves that the demise of the “antifascist” narrative that shaped the postwar period was substituted by the “free market” one in European memories, which enabled the articulation of opinions whose expression was not accepted without difficulty in the public sphere. The rise of far-right movements across Europe makes all the more pertinent the comprehension of the economic exploitation and ideological factors that shaped conflicting memories. We hope that the research from the perspective of postwar Jewish experience and its comparative dimension paves the way for the enrichment of the research agenda and will allow us to better understand our contemporary world and those who made it.